NFKB1 Signalling Activation Contributes to TRPV1 Over-expression via Repressing MiR-375 and MiR-455: a Study on Neuropathic Low Back Pain - Li, Z; Zhou, Y; Li, Z (Folia biologica (Praha), 2022)
Transient receptor potential cation channel subfamily V member 1 (TRPV1) has been found over-expressed in low back pain (LBP) patients with neuropathic pain (NP), but the underlying mechanism is still unclear. In the present study, the up-regulation of the TRPV1 protein level in sinuvertebral nerve biopsies from patients with NP was verified by immunoblotting, but the TRPV1 mRNA level was not significantly changed. MiRNAs targeting TRPV1 mRNA were predicted by a bioinformatic tool, and the interactions between the miRNAs and TRPV1 were confirmed by dual luciferase assay. The correlation between NFKB1 signalling and TRPV1 expression was analysed and confirmed by using sNF96.2 cells after lipopolysaccharide stimulation. We found that five out of 18 miRNAs repressed TRPV1 expression, and the levels of miR-375 and miR-455 were negatively correlated with the protein level of TRPV1 in patients with NP. MiR-375 and miR-455 were identified to repress TRPV1 expression via targeting the 3'UTR of TRPV1 mRNA. NFKB1 signalling activation down-regulated the expression of miR-375 and miR-455, and thus up-regulated the TRPV1 protein level. In conclusion, we partially unveiled the mechanism of how TRPV1 is over-expressed in chronic LBP patients with NP and provided two potential candidate miRNAs for NP treatment.
Keywords: signální transdukce; upregulace; Signal Transduction; mikro RNA; RNA, Messenger; kationtové kanály TRPV; TRPV Cation Channels; Humans; messenger RNA; lidé; Up-Regulation; NF-kappa B p50 Subunit; lumbalgie; Low Back Pain; MicroRNAs; NF-kappa B - podjednotka p50